Sistem Pengendalian dan Monitoring Distribusi Air Berbasis Nodemcu 8266 - Laxmy Devy; Yul Antonisfia; Monica Febrina; Suryadi suryadi (Elektron : Jurnal Ilmiah, 2020)
Clean water management is managed by a Perusahaan Daerah Air Minum (PDAM), which is centered on each local government. The distribution of water to consumers cannot be done evenly because of the water distribution system and manual monitoring. Overcoming these problems, the Water Distribution Equity System to Consumers can be used to monitor and control water distribution. This system regulates the debit and time zone for water distribution to consumers. Water discharge is detected by the water flow sensor, and the valve is connected to the servo and time zone using RTC DS1307. The water pump is controlled to maintain the volume of water in the reservoir. The water level in the reservoir is detected using the HC-SR04 ultrasonic sensor. Water distribution is monitored on PCs (Personal Computers) and smartphones using Delphi programming and Thingspeak. The reading of water discharge is generated during peak use times for each faucet is 1.9: 1.8: 1.8 while at the time of normal use the ratio of the initial distribution to each faucet is 2.5: 2.3, 1: 1, and 2.5: 2.3.